Phosphatidylserine Synthase from Salicornia europaea Is Involved in Plant Salt Tolerance by Regulating Plasma Membrane Stability. (3rd November 2020) - Lv, Sulian; Tai, Fang; Guo, Jie; Jiang, Ping; Lin, Kangqi; Wang, Duoliya; Zhang, Xuan; Li, Yinxin
Abstract: Salinity-induced lipid alterations have been reported in many plant species; however, how lipid biosynthesis and metabolism are regulated and how lipids work in plant salt tolerance are much less studied. Here, a constitutively much higher phosphatidylserine (PS) content in the plasma membrane (PM) was found in the euhalophyte Salicornia europaea than in Arabidopsis. A gene encoding PS synthase (PSS) was subsequently isolated from S. europaea, named SePSS, which was induced by salinity. Multiple alignments and phylogenetic analysis suggested that SePSS belongs to a base exchange-type PSS, which localises to the endoplasmic reticulum. Knockdown of SePSS in S. europaea suspension cells resulted in reduced PS content, decreased cell survival rate, and increased PM depolarization and K + efflux under 400 or 800 mM NaCl. By contrast, the upregulation of SePSS leads to increased PS and phosphatidylethanolamine levels and enhanced salt tolerance in Arabidopsis, along with a lower accumulation of reactive oxygen species, less membrane injury, less PM depolarization and higher K + /Na + in the transgenic lines than in wild-type (WT). These results suggest a positive correlation between PS levels and plant salt tolerance, and that SePSS participates in plant salt tolerance by regulating PS levels, hence PM potential and permeability, which help maintain ion homeostasis. Our work provides a potential strategy for improving plant growth under multiple stresses.